From Toleration to Religious Freedom: Cross-Disciplinary Perspectives - van der Tol, Mariëtta (Histories of Religious Pluralism Ser., 2021)
Cover -- Table of contents -- A Dedication to Richard Bonney (1947-2017) -- Acknowledgements -- Introduction -- How Religious Freedom Became a Natural Right: The Case of Post-Reformation England (John Coffey) -- Tolerable and Intolerable Local Practices of Religion during the English Interregnum (Fiona McCall) -- The Political Arithmetic of Transmutation: Heterodoxy and Political Economy in Sir William Petty (1623-1687) (Shannon Stimson) -- Where Liberalism Begins and Toleration Ends: Locke on Atheism and Rawls on the 'Unreasonable' (Alex Tebble) -- Mutual Toleration in the English Churches: Legal Devices to Enforce Perceived Orthodoxy in Denominational Space (Augur Pearce) -- From Toleration to Religious Freedom to Toleration Again? A Historical Reflection on the Swiss Case (Sixteenth to Twenty-First Centuries) (Sarah Scholl) -- Toleration and Religious Otherness in the Early Enlightenment and Contemporary Europe (Kaisa Iso- Herttua) -- Different yet Similar: Croatian Experiences of the Integration of Its Islamic Community into Society (Mirela Krešić) -- Lutheran Legacies and the Politics of Migration: Reformation Resources for a Contemporary Conundrum (Hans Leaman) -- Toleration and Religious Freedom: From Cross-Disciplinary to Cross-Faith and Worldview (E. S. Kempson) -- Notes on Editors -- Notes on Contributors -- Index.